Immunohistochemical and histomorphometric analysis of the endometrium of rats in permanent estrus treated with melatonin, metformin and clomiphene citrate (Research, Society and Development, 2022)
Objective: To evaluate the effects of melatonin, metformin and clomiphene citrate on the endometrium of polycystic ovary syndrome model rats. Methods: Seventy-eight rats were divided into 13 groups and two experiments (prevention and treatment). After exposure, all animals were anesthetized and the uterine horns were removed and submitted to hematoxylin and eosin staining and immunohistochemistry (Ki-67 and Vegf). The data obtained were submitted to Student's t test (p